Schlegel and the Enemies of the Romantic Irony - Raga Rosaleny, Vicente (Anales del Seminario de Historia de la Filosofía, 2007)
Schlegel’s irony, which is the main author along with Solger, of irony in German romanticism, becomes a reinterpretation of the figure of the ironic Plato’s Socrates . Nevertheless, his proposal of a pragmatic irony was rejected in a violent way by Hegel and Kierkegaard, that reread Socrates and his irony in a different sense of Schlegel. For these the proposal of the romantic author was a challenge to the society that would end up destroying it, but, from our perspective such semantic reading of the schlegelian irony is very weak and, rather, the proposal of the German writer can be understood like a way of a constructive critic of the political community and we can learn much of Schlegel today.
Keywords: Scepticism; Irony; Pragmatism; Romanticism; Semantic